Dapson in the Treatment of Pyoderma Gangrenosum: a Narrative Review - Głuszak, Paweł; Beutler, Jacek; Kurkowska, Nina; Polańska, Adriana; Żaba, Ryszard; Dańczak-Pazdrowska, Aleksandra (Dermatology Review/Przegląd Dermatologiczny, 2024)
Pyoderma gangrenosum is a rare but highly debilitating dermatologic condition frequently associated with systemic disorders such as inflammatory bowel disease and rheumatoid arthritis. The clinical management of pyoderma gangrenosum is particularly challenging due to the absence of standardized diagnostic criteria and evidence-based treatment protocols, which complicates therapeutic decision-making. Dapsone, an anti-inflammatory and immunomodulatory agent, has demonstrated potential therapeutic efficacy in pyoderma gangrenosum by modulating neutrophilic activity, a key factor in the pathogenesis of this disease. This review endeavours to provide a comprehensive synthesis of clinical evidence regarding the application of dapsone in pyoderma gangrenosum management, particularly in scenarios where first-line therapies, such as glucocorticosteroids or biological agents, are contraindicated or inaccessible. Moreover, the review offers practical insights for the integration of dapsone into clinical practice.